On weighted inequalities for fractional integrals of radial functions - de Napoli, Pablo Luis (2011)
We prove a weighted version of the Hardy-Littlewood-So- bolev inequality for radially symmetric functions, and show that the range of admissible power weights appearing in the classical inequality due to Stein and Weiss can be improved in this particular case.